Aplikasi Pengenalan Sejarah dan Kebudayaan Peradaban Mesir Kuno Berbasis Augmented Reality dalam Perekonomian Masyarakat - Prayoga, Pramana Andi; Zakariyah, Muhammad (Jurnal Informatika Ekonomi Bisnis, 2024)
Ancient Egypt is an ancient civilization in northeastern Africa, centered on the lower reaches of the Nile River, an area that is now the country of Egypt. There are many historical remains from ancient Egyptian civilization. One of the famous remains of ancient Egyptian civilization is the Giza pyramid. The Pyramids of Giza are the greatest masterpieces ever created by humans in ancient times. The magnitude of the ancient Egyptian civilization makes many people interested in knowing information about this civilization. To make it easier to find out information about the ancient Egyptian civilization, an application was built with Augmented Reality technology. This application design uses the SDLC method which consists of analysis, design, programming, testing, operation and maintenance stages. This application was built by utilizing various software such as Unity 3D, Vuforia Engine, and Blender to create 3D models. This application development uses the C# programming language. This research succeeded in producing an Augmented Reality application designed for the Android platform. This application is able to display information in the form of text and 3D objects to users. The application trial was carried out using the Black Box Testing and User Acceptance method, involving 5 respondents who gave ratings from 1 to 5. The test results showed that users could use this application smoothly and the application ran according to user expectations.